Xenotransplantation and interspecies organogenesis: current status and issues - Kano, Mayuko; Mizutani, Eiji; Homma, Shota; Masaki, Hideki; Nakauchi, Hiromitsu (Frontiers in Endocrinology, 2022)
Pancreas (and islet) transplantation is the only curative treatment for type 1 diabetes patients whose β cell functions have been abolished. However, the lack of donor organs has been the major hardle to save a large number of patients. Therefore, transplantation of animal organs is expected to be an alternative method to solve the serious shortage of donor organs. More recently, a method to generate organs from pluripotent stem cells inside the body of other species has been developed. This interspecies organ generation using blastocyst complementation (BC) is expected to be the next generation regenerative medicine. Here, we describe recent advances and future prospects for these two approaches.